Exile and suffering: a selection of papers read at the 50th anniversary meeting of the Old Testament Society of South Africa OTWSA/OTSSA, Pretoria, August 2007 - Becking, Bob; Human, Dirk J. (Oudtestamentische studiën, 2008)
Sin, suffering, and sagacity : Genesis 2-3 / Gerda de Villiers -- Suffering and hope during the Exile / Jurie Le Roux -- Suffering from formlessness : the ban on images in Exilic times / Matthias Köckert -- Interrupting God-language : rethinking the image of God as liberator in Isaiah 42 / L. Juliana M. Claassens -- Myth, metaphor or memory? the allusions to Creation and Exodus in Isaiah 51:9-11 as a theological response to suffering during the Exile / Hendrik Bosman -- The assassination of Gedaliah (Jer. 40:7-41:18) / Eric Peels -- Perspective after the Exile : the King, [ʻvdj], 'My servant' in Jeremiah : some reflections on MT and LXX / Raymond de Hoop -- Exile in Hosea 9:3-6 : where and for what purpose? / Gert Kwakkel -- Perverse delight : some observations on an unpleasant theme in the Old Testament / Klaas Spronk -- Exile and pain : a chapter from the story of God's emotions / Eep Talstra -- Does exile equal suffering? a fresh look at Psalm 137 / Bob Becking -- The poetics of exile and suffering : memory and perceptions : a cognitive-linguistics study of Lamentations / Yehoshua Gitay -- The Exile as Sabbath rest : the Chronicler's interpretation of the Exile / Louis Jonker -- Lamenting the loss of lament, the language for our times / Frances Klopper -- Interpreting 'the Exile' in African Biblical scholarship : an ideo-theological dilemma in post-colonial South Africa / Gerald West